An overview of treatment for atrial septal defect with pulmonary hypertension - Gudi, Veronika Anjelina Aho; Suastika, Luh Oliva Saraswati; Sinardja, Cyndiana Widia Dewi (Malahayati International Journal of Nursing and Health Science, 2024)
Background: Atrial Septal Defect (ASD) is a congenital heart defect which can be the cause of comorbidities in the form of Pulmonary Arterial Hypertension (PAH) and therapy cannot be done simply by correcting the ASD but requires further study and evaluation.Purpose: Describe the treatment given to patients with ASD and PAH and the correlation between the administration of interventional therapy and the patient's probability of PH.Method: This study is a descriptive quantitative using a cross-sectional research design. The sampling technique was total sampling method. The samples were 41 ASD patients with PAH at Prof. Ngoerah General Hospital in Denpasar in 2022. Patients under 18 years of age and those with other congenital heart disease will be excluded. The demographic characteristics assessed were the patient's age and gender. The therapy data included information on medical therapy and intervention therapy.Results: Focus of medical therapy was supportive therapy rather than specific PAH therapy. Percutaneous ASD closure was the most widely-used intervention therapy compared to surgical ASD closure. Based on statistical analysis, the p value > 0.05 is 0.284, so there is no significant correlation between the probability of the patient's pH and the provision of intervention therapy.Conclusion: At Prof Ngoerah General Hospital Denpasar, the majority of ASD patients with complications of pulmonary hypertension were females aged between 21 to 30 years. The medical therapy given is adjusted based on the severity of PH as assessed through echocardiography examination. Majority of patients received supportive therapy compared to specific therapy for PAH. Medical therapy is prioritized for patients who have contraindication criteria for interventional therapy. Percutaneous ASD Closure was found to be the largest percentage in interventional therapy regardless of the severity, except for patients who were indicated to undergo surgical ASD closure. There is no significant relationship between the patient's PH probability level and the choice of intervention therapy.